Women academics' research productivity at one university campus: an analysis of dominant discourses - Zulu, Constance (South African Journal of Higher Education, 2016)
Universities privilege research and publication for the career advancement and academic recognition of academics. Yet, women academics face obstacles which inhibit their research productivity. Some of these obstacles or discourses have become dominant in studies of women’s research productivity. They include the demands of acquiring the doctorate and the professorate, heavy teaching loads, lack of time, family responsibilities, area of specialization, and difficulty in entering supportive networks. A review of the literature, coupled with qualitative study of a purposefully selected sample of predominantly black early career women academics at one university campus in South Africa revealed the gendered nature of these discourses across cultures and across continents. Many of these discourses are beyond the control of women academics. Universities should therefore remove structural impediments to research productivity and develop programmes to target women academics for research growth and development at all levels of their careers. Keywords: women academics; research productivity; dominant discourses